Hybrid neural networks in cyber physical system interface control systems - Sergei Sokolov; Anton Zhilenkov; Sergei Chernyi; Anatoliy Nyrkov; Nikolay Glebov (Institute of Advanced Engineering and Science, 2020)
The calculation and results of simulation of the magnetic control system for the spacecraft momentum are presented in the paper. The simulation includes an assessment of the reliability of calculating the Earth's magnetic field parameters, as well as an assessment of the quality of object stabilization by resetting the total momentum with the aid of the system under review. The outcome of a comparative analysis of resource efficiency and energy efficiency are demonstrated in the implementation of the proposed hardware models of controllers on FPGA. The strengths and weaknesses of the programming models are shown. The developed models will allow to be modified and perform more complex operations in the future.